Examining the Clinical Effectiveness of Non-Carbapenem β-Lactams for the Treatment of Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae - Allison M. Gibble; Alan E. Gross; Angela M. Huang (MDPI AG, 2015)
Treatment options for extended-spectrum β-lactamase-producing Enterobacteriaceae are limited. Piperacillin-tazobactam and cefepime represent potential alternative treatment options; however, large prospective studies are lacking. This review evaluates the current literature regarding use of piperacillin-tazobactam and cefepime for the treatment of extended-spectrum β-lactamase-producing Enterobacteriaceae. Antimicrobial stewardship programs can play a key role in guiding the best practices for the management of these challenging infections.